Multidimensional model of successful aging and nursing terminologies: similarities for use in the clinical practice - Amália de Fátima Lucena; Carla Argenta; Melissa de Freitas Luzia; Miriam de Abreu Almeida; Luciana Nabinger Menna Barreto; Elizabeth Swanson (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Aim: To compare the domains of the Multidimensional Model of Successful Aging (MMSA) with the nursing terminologies, such as, NANDA International (NANDA-I), Nursing Interventions Classification (NIC) and Nursing Outcomes Classification (NOC), in order to find similarities among them. Method: Cross-mapping between MMSA and nursing terminologies in two stages: individual analysis and comparison between the MMSA and the nursing terminologies, based on the mapping process rules; consensus among researchers to validate the results. Results: All NOC and NIC domains were mapped with similarity in the MMSA domains, and 12 of the 13 NANDA-I domains showed similarity to the MMSA domains. In addition, similarity was identified between MMSA and most classes of the three classifications. Conclusions: The similarity between MMSA, NANDA-I, NIC and NOC supported the idea that the MMSA framework can be used in the nursing process to qualify the nursing practice in the elderly care.